2008
DOI: 10.1002/ijc.23310
|View full text |Cite
|
Sign up to set email alerts
|

Pure antiestrogen‐induced G1‐arrest in myeloma cells results from the reduced kinase activity of cyclin D3/CDK6 complexes whereas apoptosis is mediated by endoplasmic reticulum‐dependent caspases

Abstract: Multiple myeloma (MM) is a malignancy characterized by the accumulation of tumoral plasma cells in bone marrow. This disease remains incurable and the development of new therapeutic strategies is urgently required. We have studied the effects of 2 selective estrogen receptor disrupters (SERDs), RU 58668 (RU) and ICI 182,780 (ICI) or pure antiestrogens (AEs) on MM cell lines. Both compounds have antimyeloma activity through either cell cycle arrest or induction of apoptosis. To analyze the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…This effect was found at a lower extent after treatment with free 4HT. This supports a greater extent of cellular uptake of the liposomeencapsulated AE and may reflect an enhanced reticulum endothelium-mediated caspase apoptosis process as indicated previously (18). These results are in agreement with the enhancement of the cellular capture of the other AE RU once entrapped in liposomes, a process also reported to bypass the extrusion capacity of Pgps (33).…”
Section: Enhanced Anti-proliferative Activity Of 4ht Ph-gradient Liposupporting
confidence: 90%
See 1 more Smart Citation
“…This effect was found at a lower extent after treatment with free 4HT. This supports a greater extent of cellular uptake of the liposomeencapsulated AE and may reflect an enhanced reticulum endothelium-mediated caspase apoptosis process as indicated previously (18). These results are in agreement with the enhancement of the cellular capture of the other AE RU once entrapped in liposomes, a process also reported to bypass the extrusion capacity of Pgps (33).…”
Section: Enhanced Anti-proliferative Activity Of 4ht Ph-gradient Liposupporting
confidence: 90%
“…Depending on the cell line, different AEs arrest progression of the cell cycle and/or induce apoptosis (15)(16)(17). For examples, 4HT arrests cell cycle and induces apoptosis in LP-1 MM cells, while the selective estrogen receptor down-regulators (SERDs) RU 58668 (RU) and Faslodex® induce only apoptosis in RPMI8266 MM cells (17)(18)(19). Raloxifen acts like 4HT for arresting cell proliferation and inducing apoptosis in MM cells (20).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that AEs belonging to both SERD and SERM classes display anti-proliferative and/or pro-apoptotic properties on MM cell lines and primary cells [ 5 , 7 ]; these effects are dependent on AEs and cell lines ( Supplementary Table 1 ). Roughly, OHT induces both G1 arrest and apoptosis in responsive HMCLs, while pure AEs such as RU 58668 and fulvestrant induce either G1 arrest or apoptosis, suggesting that each AE subtype does not affect identical pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Selective estrogen receptor modulators (SERMs) and selective estrogen receptors disruptors (SERDs) or pure antiestrogens (AEs) may provide a potent strategy in myeloma therapy. Indeed, several groups, including our, have previously reported that SERMs and SERDs inhibited cell proliferation and/or induced apoptosis of MM cells [ 3 - 7 ]. Although myeloma cells express estrogen receptors (ER) belonging to both α and β isotypes [ 4 , 5 ],it is not clear if AEs signal through canonical ERs.…”
Section: Introductionmentioning
confidence: 99%